Uso fertilizante do subproduto da agroindústria processadora de goiabas I: atributos químicos do solo - Souza, Henrique Antunes De; Rozane, Danilo Eduardo [UNESP]; Amorim, Daniel Angelucci De; Modesto, Viviane Cristina [UNESP]; Natale, William [UNESP] (Sociedade Brasileira de Fruticultura, 2014)
The use of alternative sources of nutrients coming especially from waste and industrial by-products can be an important strategy in nutrient cycling, ensuring proper destination of materials that would otherwise be discarded. The objective was to evaluate the application of doses of by-product of guava processing industry on fertility of an Ultisol in a guava orchard. Doses of waste were established on the basis of N content in the material. The experimental design was a randomized block design with five treatments and four replications, the doses of the residue equal to zero, 9, 18, 27 and 36 t ha-1 (dry weight of the material). There were five applications residue: in 2006, 2007, 2008, 2009 and 2010. The by-product of the guava processing industry promoted changes in soil fertility in the orchard. With increasing doses increased the concentrations of phosphorus in the soil in all analyzes. The manganese concentrations increased and decreased the soil pH value in the last years of the experiment. It was observed in the subsuperfical layer (0.20-0.40 m) after continuous application of by-product an increase in phosphorus concentration as a function of the doses of the by-product.

A utilização de fontes alternativas de nutrientes, provenientes especialmente de resíduos e subprodutos da agroindústria, pode ser estratégia importante na ciclagem de elementos essenciais, garantindo destino adequado de materiais que seriam descartados. Assim, objetivou-se avaliar a aplicação de doses do subproduto da indústria processadora de goiabas sobre a fertilidade de um Argissolo, sob pomar de goiabeiras. As doses de resíduo foram estabelecidas em função dos teores de N no material. O delineamento empregado foi o de blocos casualizados, com cinco tratamentos e quatro repetições, sendo as doses do resíduo (moído) iguais a: zero; 9; 18; 27 e 36 t ha-1 (peso do material seco). Foram feitas cinco aplicações do subproduto em: 2006, 2007, 2008, 2009 e 2010. O subproduto da indústria processadora de goiabas promoveu alterações na fertilidade do solo do pomar. Com o aumento das doses, houve incremento das concentrações de fósforo no solo em todas as análises realizadas. As concentrações de manganês aumentaram, e houve redução do valor pH do solo nos últimos anos de condução do experimento. Observou-se, na camada subsuperfical (0,20-0,40 m), após a aplicação contínua do subproduto, aumento na concentração de fósforo em função das doses do subproduto.
Agronomic use of by-product of guava processing industry: I - chemical soil properties
Keywords: Psidium guajava; Adubação; Fertilidade do solo; Psidium guajava; Fertilization; Fertility of soil